DEVELOPMENT AND PSYCHOMETRIC TESTING OF AN INSTRUMENT TO MEASURE WOMEN'S PERCEPTIONS OF UNPLANNED PREGNANCY. Issue 3 (2nd October 2018) - Mohammadi, Eesa; Nourizadeh, Roghaiyeh; Simbar, Masoumeh; Baghestani, Ahmad Reza; Rohana, Nicole
Abstract: A woman's decision to continue or terminate an unplanned pregnancy is affected by a broad range of contextual and cognitive factors. The identification of women's perceptions of unplanned pregnancy is crucial for health care providers to be able to offer supportive care and counselling. The aim of this study was to develop an instrument to accurately measure women's perceptions of unplanned pregnancy: the Women's Perceptions of Unplanned Pregnancy Questionnaire. The instrument was developed using a methodological framework guided by Waltz et al. (2010 ). A conceptual model of the designed instrument emerged from the qualitative study using a content analysis approach conducted in Tabriz, Iran. Participants were recruited using convenience sampling method between June 2016 and July 2017. Participants were a sample of married Iranian women between the ages of 15 and 49 who had experienced an unplanned pregnancy, either unwanted or mistimed, within the last 3 months. Women with an established diagnosis of a psychological disorder were excluded from the study. The psychometric properties of the instrument were assessed using face, content, concurrent and construct validations. To evaluate face validity, qualitative and quantitative (item impact score) methods were used. The content validity was assessed by fifteen panel experts. In addition, concurrent validity of the designed instrument was tested using the Persian version of the Cambridge Worry Scale and the Spielberger State-Trait Anxiety Inventory. The construct validity was calculated by using the exploratory factor analysis method. Data were collected from questionnaires completed by 310 eligible women. Analysis of the data using exploratory factor analysis yielded 31 items in a unique six-factor structure. The instrument was found to have high internal consistency (Cronbach's α=0.88) and adequate reliability (Intraclass Correlation Coefficient=0.89). A clearer understanding of women's perceptions of unplanned pregnancy may enhance reproductive services and interventions.